Pengaruh Puntiran Per Inchi Benang Roving Dan Regangan Belakang Mesin Ring Spinning Terhadap Ketidakrataan Benang Kapas 100 % Carded Ne1 20’s - Giyanto, Giyanto; Huda, Huda (Universitas Islam Syekh Yusuf Tangerang, 2025)
arn unevenness is a parameter of yarn quality. Uneven yarn indicates that the yarn has thick and thin sections. Uneven yarn, when made into fabric, will result in poor fabric evenness, thus lowering the resulting fabric's grade. A low-grade fabric will affect its selling price. Therefore, it is important to find solutions to obtain yarn with better evenness. The research was conducted on a ring spinning machine using a randomized block design with three replications. The factors studied included twists per inch of roving yarn, consisting of twists of 0.96, 1.0, and 1.04, and backstretch on the ring spinning machine, consisting of backstretch of 1.13, 1.22, and 1.31. Analysis of variance (ANOVA) was used to determine which treatment was best. Since the desired yarn unevenness value is as low as possible, the lower the better the criterion. The experimental results showed that setting the roving yarn twist count to 0.96 per inch and the ring spinning machine's backstretch to 1.22 times resulted in the lowest yarn unevenness value, at 10.51.